Changes in the technical and scale efficiency of rice production activities in the Mekong delta, Vietnam - Diep, Thanh Tung; Justus Liebig University Giessen (My University, 2013)
I used bootstrapping data envelopment analysis (DEA) to measure changes in technical and scale efficiency in rice production in the Mekong delta region, Vietnam. The data include sample production sets from 1998 and bi-annual updates from 2002 to 2010. Technical efficiency changed significantly over this period, showing an upward trend. On the other hand, increasing return to scale is dominant trend, which reflects the need to increase the rice production scale generally and expand land use particularly. Meanwhile, the government has been trying to prevent land consolidation activities and restrict production scales using quotas and agricultural land use duration rules.
Keywords: Data envelopment analysis; technical efficiency; bootstrap; returns to scale; rice production; Mekong delta; ddc:630